Swarm-TEC Satellite Measurements as a Potential Earthquake Precursor Together With Other Swarm and CSES Data: The Case of Mw7.6 2019 Papua New Guinea Seismic Event - Akhoondzadeh, Mehdi; De Santis, Angelo; Marchetti, Dedalo; Shen, Xuhui (Frontiers in Earth Science, 2022)
On May 14, 2019, a strong Mw=7.6 shallow earthquake occurred in Papua New Guinea. This paper explores for the first time the analysis of Total Electron Content (TEC) products measured for six months by GPS antenna onboard Swarm satellites, to detect possible seismo-ionospheric anomalies around the time and location of the above mentioned earthquake. The night time Vertical TEC (VTEC) time-series measured using Swarm satellites Alpha and Charlie, inside the earthquake Dobrovolsky’s area show striking anomalies 31 and 35 days before the event. We successfully verified the possible presence of concomitant anomalous values of in-situ electron density detected by the new Chinese satellite dedicated to search for electromagnetic earthquake precursors (CSES-01). On the other hand, the analysis of VTEC night time measured by Swarm Bravo shows gradual and abnormal increase of the VTEC parameter from about 23 days before the earthquake which descends 3 days before the earthquake and reaches its lowest level around the earthquake day. We also analyzed time series and tracks of other six in-situ parameters measured by Swarm satellites, electron density from CSES and also GPS-TEC measurements. As it is expected from the theory, the electron density anomalous variations acknowledge the Swarm VTEC anomalies, confirming that those anomalies are real and not an artifact of the analysis. The comparative analysis with measurements of other Swarm and CSES sensors emphasizes striking anomalies about 2.5 weeks before the event, with a clear pattern of the whole anomalies typical of a critical system as the earthquake process is for Earth. A confutation analysis outside the Dobrovolsky area and without significant seismicity show no anomalies. Therefore based on our study, VTEC products of Swarm satellites could be an appropriate precursor beside the other measured plasma and magnetic parameters using Alpha, Bravo and Charlie Swarm and CSES satellites that can be simultaneously analysed to reduce the overall uncertainty.